Associations of co‐occurring psychosocial and lifestyle factors with multisite musculoskeletal pain during late adolescence—A birth cohort study. (27th May 2019) - Heikkala, Eveliina; Paananen, Markus; Taimela, Simo; Auvinen, Juha; Karppinen, Jaro
Abstract: Background: Musculoskeletal (MS) pain is common. It often exists in several sites and is recurrent. Psychosocial difficulties and unhealthy behaviours have been related to multisite MS pain, but no literature has assessed the impact of accumulated psychosocial and lifestyle factors on recurrent multiple MS pain. Methods: Our data were gathered from two questionnaires of the well‐known Northern Finland Birth Cohort 1986 (NFBC1986), sent to members when they were aged 16 and 18. A total of 1, 625 adolescents (712 boys and 913 girls) answered questions on smoking, physical activity, sedentary behaviour, sleeping and emotional and behavioural problems at 16 years and on musculoskeletal pain at 16 and 18 years. Weight and height measurements were taken at a health examination at baseline. A latent class analysis and multinomial regression analysis were conducted. Results: We identified four clusters among both sexes. "Externalizing behavior" among both genders (OR 2.98, CI 1.73–5.13 among boys; OR 2.38, CI 1.38–4.11 among girls), "Multiple risk behaviors" among girls (OR 2.73, CI 1.30–5.71) and a "Sedentary" cluster among boys (OR 1.85, CI 1.21–2.82) were associated to recurrent multisite MS pain. "Obese" clusters had no significant associations with recurrent multiple MS pain. Conclusions: Adolescents with psychosocial difficulties and/or several adverse health behaviours were at an increased risk of recurrent multisite MS pain, which emphasizes the importance of simultaneously studying multiple rather than single factors. The identification of risk groups may help more accurately target preventive interventions. Significance: This study found subgroups of adolescents at risk of recurrent multisite musculoskeletal pain during late adolescence. The accumulation of multiple adverse behaviours is likely to provide new perspectives for understanding the multidimensional nature of multiple MS pains.